2011
DOI: 10.1016/j.brat.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Worry in imagery and verbal form: Effect on residual working memory capacity

Abstract: Worry-prone individuals have less residual working memory capacity during worry compared to low-worriers (Hayes, Hirsch, & Mathews, 2008). People typically worry in verbal form, and the present study investigated whether verbal worry depletes working memory capacity more than worry in imagery-based form. High and low-worriers performed a working memory task, random interval generation, whilst thinking about a worry in verbal or imagery form. High (but not low) worriers had less available working memory capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
136
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(167 citation statements)
references
References 52 publications
15
136
15
1
Order By: Relevance
“…This relationship between perfectionistic concerns and working memory capacity corroborates previous studies relating worry and lower working memory capacity for neutral stimuli (e.g., Leigh & Hirsch, 2011;Trezise & Reeve, 2016). Moreover, recent studies found that individuals with lower working memory capacity recall more critical lures than individuals with high levels of working memory (e.g., Bixter & Daniel, 2013).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This relationship between perfectionistic concerns and working memory capacity corroborates previous studies relating worry and lower working memory capacity for neutral stimuli (e.g., Leigh & Hirsch, 2011;Trezise & Reeve, 2016). Moreover, recent studies found that individuals with lower working memory capacity recall more critical lures than individuals with high levels of working memory (e.g., Bixter & Daniel, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…Numerous behavioral and neuroimaging studies suggest that worry is responsible for the detrimental effect of anxiety on working memory, and executive functioning in particular (e.g., Collette & Van der Linden, 2002;Crowe, Matthews, & Walkenhorst, 2007;Hayes, Hirsch, & Mathews, 2008;Leigh & Hirsch, 2011;Trezise & Reeve, 2016). To account for the restricted working memory capacities associated with worry, it has been suggested (Leigh & Hirsch, 2011) that depleted working memory resources during worry may be relevant to the persistence and perceived uncontrollability of worry.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%
See 1 more Smart Citation
“…Lastly, the moderational of working memory by age was rather surprising, especially given that several studies have found positive associations between worry and this dimension of executive functioning in adult populations [30,54]. It is unclear why this relationship would not be significant at a certain point in childhood only to reemerge at a later stage of development.…”
Section: Discussionmentioning
confidence: 88%
“…Dentre as funções cognitivas estudadas pela neuropsicologia, a memória de trabalho (MT) vêm se destacando por sua complexidade e alta relação com demais processos neuropsicológicos (Baddeley, 2010;Baddeley, Allen, & Vargha-Khadem, 2010;Cabeza et al, 2004;Leigh & Hirsch, 2011;Levens, & Gotlib, 2010). Esse domínio cognitivo constitui-se em um sistema ativo, composto por múltiplos componentes, que possuem a capacidade de armazenar informações por um tempo limitado (de alguns segundos a um ou dois minutos), mas suficiente para manipular uma ampla variedade de informações durante o processamento de tarefas cognitivas complexas (Baddeley, 2003).…”
unclassified